2011
DOI: 10.1007/s00213-011-2264-x
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of alcohol on feedback processing and outcome evaluation during risky decision-making: an ERP study

Abstract: RationaleAlthough risky decision-making is one of the hallmarks of alcohol use disorders, relatively little is known about the acute psychopharmacological effects of alcohol on decision-making processes.ObjectiveThe present study investigated the acute effects of alcohol on neural mechanisms underlying feedback processing and outcome evaluation during risky decision-making, using event-related brain potentials (ERPs).MethodsERPs elicited by positive and negative feedback were recorded during performance of a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 69 publications
(87 reference statements)
7
87
0
2
Order By: Relevance
“…However, it is important to note that to my knowledge, the impact of acute intoxication on the SLT has not been investigated to date. Moreover, although previous research has found intoxication effects on the BART , other null findings in this area could indicate that the BART may lack the sensitivity to detect any effects of acute alcohol consumption (Euser et al, 2011;Peacock et al, 2013; S. C. Reed et al, 2012). …”
Section: Preliminarymentioning
confidence: 91%
See 2 more Smart Citations
“…However, it is important to note that to my knowledge, the impact of acute intoxication on the SLT has not been investigated to date. Moreover, although previous research has found intoxication effects on the BART , other null findings in this area could indicate that the BART may lack the sensitivity to detect any effects of acute alcohol consumption (Euser et al, 2011;Peacock et al, 2013; S. C. Reed et al, 2012). …”
Section: Preliminarymentioning
confidence: 91%
“…Furthermore, some studies find negligible effects of intoxication overall on risk taking (Euser, Van Meel, Snelleman, & Franken, 2011;Peacock, Bruno, Martin, & Carr, 2013).…”
Section: Whisky To Riskymentioning
confidence: 99%
See 1 more Smart Citation
“…Since previous ERP studies with the BART [15,21,22] used frontocentral channels, we chose E11 (identical to Fz position), E6 (identical to FCz position) and Cz for statistical analysis. Moreover, the FRN appeared to be the largest in these positions.…”
Section: Eeg Measurement and Analysismentioning
confidence: 99%
“…The FRN most likely related to the functional interaction between the posterior medial frontal cortex and the lateral prefrontal cortex [14]. The FRN is usually followed by a P3 indicating the elaboration of feedback [15].…”
Section: Introductionmentioning
confidence: 98%